Sequelae of unreplaced tooth loss in orthodontic patients: A cross-sectional study in Najran, Kingdom of Saudi Arabia - Bandar Alyami (Wolters Kluwer Medknow Publications, 2023)
Background: The early tooth loss has an adverse effect on the overall well-being of an individual. The aim of the current study was to highlight the orthodontic complications of long-term tooth loss in the city of Najran. Materials and Methods: This was a cohort study of patients presenting for orthodontic rehabilitation. A total of 326 patients that presented for orthodontic rehabilitation were examined clinically and data such as age, gender, number of missing teeth, missing teeth, duration of missing teeth, tipping, and overerupted and rotated teeth were recorded. Patients that can be treated with orthodontic space closure were excluded from the study. Patients' data were analyzed using IBM SPSS Statistics and results were presented as simple frequencies and descriptive statistics. Results: Out of 326 patients that presented for orthodontic rehabilitation, 259 patients had missing teeth with its sequelae that will demand prosthodontic rehabilitation with a prevalence rate of 79.4%. There are 97 (37.5%) males and 162 (62.5%) females with M:F ratio of 1:1.7. The age ranged from 15 to 52 years with mean ± standard deviation (28.5 ± 8.5). The age group 21-30 years constitutes the group with the highest number of missing teeth. A total number of 595 (60.2%) teeth were missing, 173 (17.5%) teeth were tipped, and 124 (12.5%) teeth were overerupted, whereas only 97 (9.8%) teeth were rotated (n = 989). Fixed orthodontic appliances (FOAs) were used for all cases with rotation and FOAs + Mini Screws were used for all cases with tipping, overeruption, and/or combinations. The dental loss was managed by prosthesis depending on patients' choice and financial capability ranging from removable/fixed prosthesis and dental implants. Conclusion: Orthodontic consequences of early tooth loss include tipping and rotation of adjacent teeth and overeruption of opposing teeth. Early acknowledgment of tooth replacement after tooth loss is essential in preventing long-term orthodontic adverse effects.